Stadium, Theatre, Prison: Ways of seeking »sports space«. - Bale, John (Forum for Idræt, 2004)
The stadium can be read in a variety of ways. The metaphors of theatre, the garden and prison are used to illustrate the relations between players and spectators, ‘nature’ and ‘culture’, and freedom and constraint. The application of such metaphors reveals the stadium as a site of ambiguity.